Delhi then & Delhi now - Dilip Bobb; Narayani Gupta; Pramod Kapoor (New Delhi : Roli Books, 2019)
Two extensive essays trace the story of Delhi from the days when it was known by other names Indraprastha, Firozabad, Dinpanah to its reincarnation as New Delhi.
Keywords: Photography; New Delhi; Illustrated works